Protein Microarrays: Technological Aspects, Applications and Intellectual Property - Dasilva, Noelia; Diez, Paula; Gonzalez-González, Maria; Matarraz, Sergio; M. Sayagues, J.; Orfao, Alberto; Fuentes, Manuel (Recent Patents on Biotechnology, 2013)
Over the last decade, proteomics has undergone remarkable progress thanks to the technical advances made in the field. Improvements in the design of the protein microarrays, including more types of chemical groups for surface functionalization, new capture agents and novel detection strategies, among others, have allowed the detection of proteins in a robust, specific, sensitive, real time and high throughput manner. However, there are still problems that hinder the analysis of low abundance proteins or those present in complex samples. For this reason, the development of patents related to the features mentioned above has an important relevance. In this review, we focus on the study of recently approved patents that try to solve the existing problems. Thanks to them, it is expected that the identification of disease biomarkers can be made in a suitable and reliable way, and above all, biocompatible and environmentally friendly.
Keywords: target protein